Osteoid Osteoma Treated with Radiofrequency Ablation - Çakar, Murat (Adv Orthop, 2015)
Purpose. Our aim is to evaluate the results of treatment with computed tomography (CT) guided percutaneous radiofrequency ablation for osteoid osteomas which were localized in a difficult area for operation. Materials and Methods. Glenoid, distal tibia, humerus shaft, proximal humerus, and in third finger of the hand proximal phalanx were involved in one patient. Proximal femur was involved in three patients, distal femur was involved in three patients, and proximal tibia was involved in two patients. 9 males and 4 females were aged 4 to 34 years (mean age: 18.5 years). All patients had pain and were evaluated with X-rays, CT, bone scintigraphy, and MRI. In all patients, RF ablation was performed with local anesthesia. The lesion heated to 90°C for 6 minutes. Results. All of the patients achieved complete pain relief after ablation and were fully weight bearing without any support. In all patients, there was soft tissue edema after the procedure. During follow-up, all patients were free from the pain and there was no sign about the tumor. There was no other complication after the process. Conclusion. CT guided RFA is a minimally invasive, safe, and cost-effective treatment for osteoid osteoma placed in difficult area for surgery.